Earning management practices in Islamic banking in Indonesia - Siti Chanifah; Hamdani .; Mutiara Wiedyaningtias (STIE Binaniaga, 2020)
This study discusses to study earnings management practices in Islamic banking which are listed on the Indonesia Stock Exchange for the 2012-2016 period. Research using quantitative descriptive. The population in this study is the Islamic banking sector in Indonesia. Research samples at 11 Sharia Commercial Banks (BUS) reported on the Indonesia Stock Exchange. The data analysis technique used is descriptive analysis, with earnings management calculations using the Friedlan Model. The variable analyzed is earnings management using discretionary accruals. The results of this study show how earnings management practices occur in 11 Islamic banks in Indonesia. Value-added positive discretionary accruals indicate that there are earnings management practices by increasing earnings or increasing revenue and negative value discretionary accruals values indicate how earnings management practices by decreasing earnings or income decreases. Keywords: Earnings Management, Discretionary Accruals, Islamic Banking